"I will sample until things get better – or until I die." Potential and limits of citizen science to promote social accountability for environmental pollution. (September 2022) - Ruppen, Désirée; Brugger, Fritz
Highlights: We use political ecology scholarship to overcome social accountability theory's apolitical nature and narrow local focus; this allows us to identify the structural power and stakeholders decisive for the success of a social accountability initiative. We present a water pollution case from a mining area in Zimbabwe to show how citizen science reinforces social accountability initiatives and strengthens community members' stance towards local authorities and corporations. We identify the power relations between the most important public and private stakeholders in the Zimbabwean coal supply chain from local to transnational levels and explain the limits of community engagement. We show that multinational clients are important benchmarking authorities for local industries and could become key pro-accountability allies of community interventions. Abstract: Mining can cause harm to both human health and ecosystems. Regulators in low-income countries often struggle to enforce decent environmental standards due to financial, technical, and personal capacity constraints and political capture. In such settings, social accountability strategies are often promoted through which citizens attempt to hold governmental and private actors directly to account and demand better governance. However, social accountability initiatives are rarely effective. We demonstrate how political ecology analysis can inform social accountability theory and practice by identifying the power structures that define the potentials and limits of a social accountability strategy. We study the coal mining area of Hwange in Western Zimbabwe, where mining not only supplies coal to power plants and factories of multinational companies but also pollutes the Deka River. Together with local community monitors, we implemented the first citizen science project conducted in Zimbabwe and identified the sources and extent of the pollution. The scientific data strengthened the community monitors' advocacy for a cleaner environment and empowered them in their exchanges with the companies and the environmental regulator. However, only some of their demands have been met. The political ecology analysis, spanning from the local to transnational levels, reveals why local social accountability initiatives are insufficient to spring the low-accountability trap in a state captured by a politico-military elite, and why corporate governance regimes have not been successful either. We argue that pro-accountability networks are more effective when they include complementary players such as multinational enterprises, provided their responsible procurement approach moves from a corporate risk management to a developmental logic.